Maryam Jameelah’s Study of “Reconstruction of Religious Thought in Islam” by Allāma Muhammad Iqbāl and “The Spirit of Islam” by Sayyid Ameer ‘Alī (Al-Qamar, 2019)
Maryam Jameelah is a well-known literary figure and she wrote on diverse topics regarding the Islamic thought. She was a critique writer of the west but with that she also wrote about the subjects that are conflicting the Islamic conventional view. As she pointed out various weaknesses in the Muslim Ummah regarding their imitation of western ideas in the name of reformation and in order to get themselves modernized in the current era and the conduct of their political regimes under the influence of western political thought or under the influence of imperial powers. In this article her view of Iqbal’s reconstruction of Islam has been critically analyzed, so this is a critique of his book “Reconstruction of Religious Thought in Islam,” with this the book by Sayyid Ameer Ali entitled “The Spirit of Islam” also critically analyzed by her. She also included in her critique the views of H.A.R. Gibb a well reputed orientalist who has discussed the approach of both the above mentions works in his book “Modern Trends in Islam” and found some diversions from the traditional Islamic belief. Being a professor of Arabic at Oxford University his arguments are also very critical on the subject.
Keywords: Maryam Jameelah; Iqbāl; Sayyid Ameer ‘Alī